The Sustainable Environment in Uruguay: The Roles of Financial Development, Natural Resources, and Trade Globalization - Awosusi, Abraham Ayobamiji; Xulu, Nkosinathi G.; Ahmadi, Mohsen; Rjoub, Husam; Altuntaş, Mehmet; Uhunamure, Solomon Eghosa; Akadiri, Seyi Saint; Kirikkaleli, Dervis (Frontiers in Environmental Science, 2022)
As the world continues to be a globalized society, there have been variations in environmental quality, but studies including trade globalization into the environmental policy framework remain limited. Therefore, employing the time series dataset of Uruguay over the period between 1980 and 2018, this current study investigates the effect of trade globalization, natural resources rents, economic growth, and financial development on carbon emissions. By employing the bounds testing procedures in combination with the critical approximation p-values of Kripfganz and Schneider (2018), ARDL estimators, and spectral causality test to achieve the goal of this research. The outcomes of the ARDL bounds test confirm a longrun connection between carbon emissions and its determinants. Moreover, from the outcome of the ARDL approach, we observed that trade globalization, economic growth, natural resources contribute to carbon emissions in Uruguay. Furthermore, we uncover that financial development does not impact environmental deterioration in Uruguay. The outcome of the spectral causality test detected that trade globalization, economic growth, and natural resources forecast carbon emissions with the exclusion of financial development. Based on the outcome, this study suggests that policies should be tailored towards international trade must be reassessed, and the restrictions placed on the exportation of polluting-intensive commodities must be reinforced